Pattern of ventilation during exercise in chronic heart failure. Issue 6 (1st June 2003) - Witte, K K A; Thackray, S D R; Nikitin, N P; Cleland, J G F; Clark, A L
Abstract : Objective: To determine the pattern of the abnormal ventilatory response in heart failure and how it relates to symptoms by looking at tidal volume (Vt ) and frequency ( f ) during exercise. Methods: 45 patients with heart failure and 21 controls underwent maximal treadmill based exercise testing with metabolic gas exchange analysis. The relation of ventilation (V̇E) to Vt was plotted to look for an inflection point where Vt failed to increase further. The slope of the relation before this inflection point was documented. Time to the inflection point, Vt, and f at the inflection point were recorded. The relation of symptom scores to f and V̇E was also examined. Results: Peak oxygen consumption (PV̇o 2 ) (mean (SD)) was lower (19.7 (4.5) v 37.9 (8.6) ml/kg/min; p < 0001) and the ventilation to carbon dioxide production (V̇E/V̇co 2 ) slope was steeper (40.0 (6.5) v 26.0 (1.6); p < 0.0001) in patients with heart failure than in the control group. The patients reached the inflection point of the V̇E/Vt slope sooner during exercise than the controls (271 (110) v 502 (196) seconds; p < 0.0001). Patients had a higher f and a smaller Vt at that point and throughout exercise until the peak where f was the same for patients and controls. Vt at the inflection point correlated with PV̇o 2 ( r = 0.67; p < 0.0001). Despite having an increased sensation of breathlessness for a given V̇E, patients were less symptomatic of f than controls. Conclusions: Patients with heart failure breathe at a higher f throughout exercise, reaching an apparent maximal Vt earlier. The Vt at an inflection point on the V̇E/Vt slope predicts PV̇o 2 .